2021
DOI: 10.15408/jkv.v1i1.20068
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol Peroxide and Stigmasterol from The Stembark of Aglaia simplicifolia (Meliaceae) and Their Cytotoxic against HeLa Cervical Cancer Cell Lines

Abstract: Two steroid compounds, ergosterol peroxide (1) and stigmasterol (2) have been isolated from the stembark of Aglaia simplicifolia belong to Meliaceae family. The chemical structures of 1 and 2 were identified based on spectroscopic evidence including UV, IR, 1D NMR, 2D NMR as well as mass spectra and by comparison with those previously reported spectra data. Both compounds were evaluated for their cytotoxic effects against cervical cancer HeLa cells in vitro. Compounds 1 and 2 showed cytotoxicity activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The isolated stigmasta-5-22-dien-3-ol ( 5 ) and tetradecyl ( E )-ferulate ( 8 ), with IC 50 values of 226.9 µM and 223.1 µM, respectively, did not show any cytotoxicity activity against MCF-7 ( Table 1 ). In another study, Stigmasta-5-22-dien-3-ol ( 5 ) showed cytotoxicity effects against oral epithelial carcinoma cells (KB/C152) with an IC 50 value of 81.18 μg/mL [ 20 ] and against HeLa cervical cancer cells with an IC 50 value of 26.42 µM [ 35 ]. (3 β )-3-Acetoxyolean-12-en-28-oic acid ( 7 ) and tetradecyl ( E )-ferulate ( 8 ) exhibited low cytotoxicity against triple-negative breast cancer (HCC70) with IC 50 values of 146.8 µM and 128.2 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The isolated stigmasta-5-22-dien-3-ol ( 5 ) and tetradecyl ( E )-ferulate ( 8 ), with IC 50 values of 226.9 µM and 223.1 µM, respectively, did not show any cytotoxicity activity against MCF-7 ( Table 1 ). In another study, Stigmasta-5-22-dien-3-ol ( 5 ) showed cytotoxicity effects against oral epithelial carcinoma cells (KB/C152) with an IC 50 value of 81.18 μg/mL [ 20 ] and against HeLa cervical cancer cells with an IC 50 value of 26.42 µM [ 35 ]. (3 β )-3-Acetoxyolean-12-en-28-oic acid ( 7 ) and tetradecyl ( E )-ferulate ( 8 ) exhibited low cytotoxicity against triple-negative breast cancer (HCC70) with IC 50 values of 146.8 µM and 128.2 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%